Pluralism and the Mind: Consciousness, Worldviews, and the Limits of Science by Matthew Colborn - McDaniel, Stan (Journal of Scientific Exploration, 2012)
Matthew Colborn’s book on what might seem a topic radically unrelated to the above quote nevertheless might have used Rodney King’s much-cited comment as its theme. In the areas of cognitive science and philosophy of mind, there is plenty of conceptual head-bashing going on as multiple views contend. The conflict is more acute than in typical disputes among philosophical positions. Where science stands in relation to this conflict of ideas lies in the advent of neuroscience transformed by the marriage of functional magnetic resonance imaging (fMRI) with the computer model of the brain. By finding that the activity of more or less discrete areas of the brain can be correlated with more or less imprecisely defined mental functions, and by assuming that the brain is a digital machine, the conclusion is drawn that the mind, self, and consciousness are now entirely within the purview of neuroscience. It follows that all other theories of the mind, and especially theories that appeal to spheres inaccessible to the physical sciences, are consigned to the trash heap. As a result, intentionality (meaning) must be cast out along with illusions such as freedom of will and spiritual aspiration.